ANALISIS STRATEGI PT. POS INDONESIA (PERSERO) DALAM MENGHADAPI PERSAINGAN PASAR DI MASA PANDEMI COVID19 (STUDI KASUS KANTOR POS SUKAPURA KEC. CILINCING JAKARTAUTARA) - Elva Pusfitha Sari; Muhammad Asad; Eman Sulaeman (JAMBIS : Jurnal Administrasi Bisnis, 2022)
PT. POS INDONESIA (PERSERO) is a State-Owned Enterprise (BUMN) engaged in services (Postalservices),in 2017 PT. POS INDONESIA (PERSERO) was ranked thrid,rwo years later it was shifted to the fourth Position under private companies,the reason for the shift in PT.POS INDONESIA (PERSERO)’s Position is because (Pos indonesia ) did not anticipate changes in the logistics business model. This Study aims to determine and analyze how the strategy at PT. POS INDONESIA (PERSERO) infacing market competition during the Covid-19 Pandemic. The method used in this research is descriptive qualitative method. Data collection is done by using observation,interview and documentation This research is analyzed using SWOT analysi (Strength,Weakness,Opportunity,Threat). SWOT Analysis is an analysis used to evaluate opportunities and threats in the external environment as well as the strengths and Weaknesses of the company’s internal environment. The results of this study show the IFAS score of 3.4 which means that all the forces generated can be used to compete,the EFAS score of 3.4 which means a large Positive value,so the opportunity for PT. POS INDONESIA (PERSERO) Sukapura Kec,Cilincing,North Jakarta can be used as a strength. From the SWOT diagram of the company PT. POS INDONESIA (PERSERO) Sukapura kec.Cilincing ,North Jakarta is in quadrant 3Position,nemely the company faces a very large market opportunity,but on the other hand faces several internal constraints/weaknesses.